TRANSFORMASI AKHLAK SANTRI DI ERA DIGITAL: STRATEGI DAKWAH HUMANISTIK SANTRI SENIOR DI PESANTREN - Izzah, Ahsanul; Muhid, Abdul (An-Nida : Jurnal Komunikasi Islam, 2025)
The development of digital technology has affected the behavior of the younger generation, including santri in pesantren, who face serious challenges in maintaining morals according to Islamic values. This phenomenon requires a da'wah strategy that is adaptive to the dynamics of the digital era. This article examines the role of senior santri in transforming santri morals through a humanistic da'wah approach. The method used is a literature review by analyzing literature from accredited national journals and relevant scientific sources. The results of the study show that da'wah based on exemplary behavior, empathy, interpersonal communication, and the use of digital media is an effective strategy in fostering santri character. Case studies of pesantren in East Java indicate the success of this approach in strengthening pesantren values in the digital era. The findings recommend strengthening the role of senior santri through humanistic da'wah training and wise integration of digital technology in moral development.